2015
DOI: 10.1007/s11947-015-1641-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Porosity and Thermal Treatment on Hydration of Mushrooms

Abstract: In this study, hydration of mushroom as a porous food material has been studied considering their biphasic character. It consists of a solid phase that consists of intertwined hyphae and having cell walls with a swellable polymeric matrix and a pore phase made up by the space in between the hyphae. We have investigated the hydration of mushrooms as a function of initial porosity and thermal treatment. Variation in porosity is induced by the natural variation in the growth of mushroom. Porosity is measured by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Similar to the trend of thickness of pericarp of chili peppers, wood shaving used as lining media of zeer pot refrigeration recorded significantly the best porosity (80.67%) followed by sand used as lining media of zeer pot refrigeration (74.42%) and the lowest was recorded in styrofoam used as lining media of zeer pot refrigeration (69.27%) [50].…”
Section: Porosity Of Chili Pepper Fruitssupporting
confidence: 64%
“…Similar to the trend of thickness of pericarp of chili peppers, wood shaving used as lining media of zeer pot refrigeration recorded significantly the best porosity (80.67%) followed by sand used as lining media of zeer pot refrigeration (74.42%) and the lowest was recorded in styrofoam used as lining media of zeer pot refrigeration (69.27%) [50].…”
Section: Porosity Of Chili Pepper Fruitssupporting
confidence: 64%
“…Several previous studies have reported that treatments of vegetables, especially those above mentioned, where elevated temperature is involved, may lead to substantial changes in the chemical composition of mushrooms (e.g. effect of blanching on protein content, enzyme activity and color changes reported by Deylami et al, 2016; effects of porosity and thermal treatment on hydration of mushrooms reported by Paudel et al, 2016; frying induced severe losses in protein, ash, and carbohydrates content but increased the 508 (T2) Blanching in 2% sodium chloride and 0.2% citric acid boiling solution for 2 min.…”
Section: Sampling and Preservation Treatments Of Agaricus Spp Mushroomsmentioning
confidence: 98%
“…However, the quality of the dehydrated products obtained is usually poor and it is characterized by a lower content of vitamins and other nutrients [3]. In addition, the high temperatures used induce structural changes [2]; these are more intense in high porosity products, such as the mushroom, whose porosity is between 25 and 50% according to Paudel et al [4]. All these facts, coupled both with the fact that consumers are demanding greater product quality requirements and also the need to reduce the impact industry has on the environment, have led to more interest being shown in the development of alternative drying technologies [5].…”
Section: Introductionmentioning
confidence: 99%